Patient safety and adverse events in dental practice in a Teaching Dental Clinic - Manrique-Guzmán, Jorge A. (2022)
Objective: To evaluate the frequency and distribution of adverse events that occur in the development of dental treatments performed by clinical operators of a Teaching Dental Clinic during 2015. Material and Methods: An observational and descriptive longitudinal and prospective study was carried out to evaluate the frequency of adverse events in the dental practice of Dentistry students, for which a System for the Registration and Notification of Adverse Events in Dentistry was implemented aimed at 110 clinical operators in the areas of Restorative Dentistry, Oral Surgery, Endodontics and Oral Rehabilitation during 2015. Results: 167 adverse events were reported, representing 10.18% of the total treatments performed during the monitoring and evaluation period. Common, depending on the clinical field, were “Post-restorative treatment hypersensitivity” (restorative dentistry), “Over-filling or under-filling with symptoms” (endodontics), “Post-extraction dental alveolitis” (oral surgery) and “Post-carving sensitivity for fixed prostheses (pillars)” (oral rehabilitation). Conclusions: The implementation of a registration and notification system is the starting point for the identification of the most frequent adverse events in dental practice, which is useful for defining procedures to be followed, developing protocols, and formulating guidelines for healthcare quality and safety.